2013
DOI: 10.1371/journal.pone.0071581
|View full text |Cite
|
Sign up to set email alerts
|

Light Driven CO2 Fixation by Using Cyanobacterial Photosystem I and NADPH-Dependent Formate Dehydrogenase

Abstract: The ultimate goal of this research is to construct a new direct CO2 fixation system using photosystems in living algae. Here, we report light-driven formate production from CO2 by using cyanobacterial photosystem I (PS I). Formate, a chemical hydrogen carrier and important industrial material, can be produced from CO2 by using the reducing power and the catalytic function of formate dehydrogenase (FDH). We created a bacterial FDH mutant that experimentally switched the cofactor specificity from NADH to NADPH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…1). This indication derived from the sequencing of mutants displaying improvement in overall catalytic efficiency with NADP + , obtained by saturation mutagenesis or other mutagenesis approaches in different laboratories (Serov et al 2002;Andreadeli et al 2008;Wu et al 2009b;Hoelsch et al 2013;Ihara et al 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). This indication derived from the sequencing of mutants displaying improvement in overall catalytic efficiency with NADP + , obtained by saturation mutagenesis or other mutagenesis approaches in different laboratories (Serov et al 2002;Andreadeli et al 2008;Wu et al 2009b;Hoelsch et al 2013;Ihara et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Hatrongjit and Packdibamrung (2010) had also demonstrated that the single substitution Q223D was sufficient to change substrate preference of BstFDH from NADP + to NAD + . Prior to this demonstration, other reports had highlighted the fundamental role of this residue for determining cofactor specificity: mutations D195S in Candida methylica (Gul-Karaguler et al 2001), D196A in Saccharomyces cerevisiae (Serov et al 2002), D195S in C. boidinii (Andreadeli et al 2008;Wu et al 2009a), D221G/A/S/Q in Mycobacterium vaccae N10 (Hoelsch et al 2013) and, more recently, D222Q/S/A in Pseudomonas and D227Q/S/A in Arabidopsis thaliana (Ihara et al 2013) had all been shown (singularly or in combination with other amino acid changes) to allow acceptance of NADP + or to turn substrate preference from NAD + to NADP + .…”
Section: Discussionmentioning
confidence: 96%
“…1A). The system successfully produced formate in vitro and in vivo [6]. However, the reduction of carbon dioxide by NADPH (CO 2 + NADPH !…”
Section: Introductionmentioning
confidence: 99%
“…BW25113 (1 and 5), pUC-fdoGHtst 0 /BWDD (2 and 6), pUCfdoGHtst/ BWDD(3 and 7), and pBR-fdoGHtst/BWDD (4 and 8) were cultivated under microaerobic (1-4) and aerobic(5)(6)(7)(8) conditions, and subjected to RNA extraction and quantitative PCR analysis.…”
mentioning
confidence: 99%
“…This is due to several properties: (i) abundance of formate dehydrogenases (FDHs) that can efficiently transfer reducing power from formate to NAD + 5 ; (ii) formate oxidation is practically irreversible, increasing the efficiency of NADH regeneration; (iii) formate, a small molecule, can easily cross membranes, thus being accessible within cellular compartments; and (iv) the byproduct of formate oxidation, CO 2 , is non-toxic and can be easily expelled from the system.Many biocatalytic processes rely on NADPH rather than NADH 6, 7 . Therefore, in the last 20 years multiple studies aimed at identifying FDHs that can naturally accept NADP + or engineering NAD-dependent FDHs to accept the phosphorylated cofactor [8][9][10][11][12][13][14][15][16] . While some of these studies were quite successful, the kinetic efficiencies observed with NADP + were relatively low, k cat /K M ≤ 30 s -1 mM -1 , and the specificities towards this cofactor were also not high, (k cat /K M ) NADP /(k cat /K M ) NAD ≤ 40.…”
mentioning
confidence: 99%